Дискриминантный анализ как метод поддержки принятия решений в медицинских исследованиях на примере иммуноферментного анализа у больных мочекаменной болезнью - Сергеева, Л. Н.; Бачурин, Г. В.; Строгонова, Т. В.; Коломоец, Ю. С.; Sergeeva, L. N.; Bachurin, G. V.; Strogonova, T. V.; Kolomoets, Yu. S.; Сергєєва, Людмила Нільсівна; Бачурін, Георгій Вікторович; Строгонова, Тетяна Василівна; Коломоєць, Юлія Сергіївна (My University, 2021)
The purpose of this article is to study the possibilities of discriminant analysis as a statistical decision support tool in medical research, using the example of the problem of choosing a tactics for treating patients with urolithiasis. based on the results of enzyme-linked immunosorbent assay. Discriminant analysis was carried out on an array of clinical and laboratory data of 70 patients with urolithiasis, of which two groups were formed: Group I included 36 patients who underwent conservative therapy; Group II consisted of 34 patients who underwent surgery. In the discriminant model, 11 indicators of general clinical examination of blood and urine, biochemical methods of blood testing and indicators of enzyme immunoassay were selected. The analysis of the constructed discriminant model made it possible to combine indicators of different nature into a single picture and solve the following tasks: find a combination of inflammation predictors and general analysis indicators in order to distinguish a group of patients requiring surgery from a group of conservative treatment; select the most informative indicators. Discriminant analysis showed the statistical significance of using the threshold values for the level of β2-microglobulin and NGAL-lipocalin. According to the discriminant model, a change in the level of β2-microglobulin is associated with changes in ESR parameters and the gender of patients (Wilks’ Lambda: 0.51, approx. F (4.65)=15.47, p <0.01), and lipocalin values - with indicators of ESR, interleukin and the patient’s age (Wilks’ Lambda: 0.5; F (4.65)=15.87; p <0.01). Also, according to the used model, in the early diagnosis of Urolithiasis, the level of β2-microglobulin is a more informative sign than the level of lipocalin. Thus, the combinations of parameters of general, biochemical blood analysis and indicators of enzyme-linked immunosorbent assay of urine, found using discriminant analysis, which characterize the work of the body’s defense subsystems in an acute state of the urolithiasis, may be useful in making a doctor’s decision on the choice of treatment tactics.
Discriminant analysis as a supporting method of decision-making in medical investigations on the example of the enzyme immunoassay in patients with urolithiasis
Keywords: discriminant analysis; urolithiasis; β2- microglobulin; lipocalin; biomarkers